Law, empire, and the sultan : Ottoman imperial authority and late Hanafi jurisprudence - Ayoub, Samy (New York, NY : Oxford University Press, 2019)
This text proposes that late Hanafi legal scholarship in the early modern period secured a role for the Ottoman sultanic authority in the process of lawmaking. It demonstrates that Hanafi jurists sustained and expanded Ottoman sultanic authority through careful reformulations of their own school and their engagement with new notions of governance embraced by the Ottomans.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 15, 2019).
Keywords: Law -- Turkey -- Islamic influences -- History; Islamic law -- Turkey -- Interpretation and construction -- History; Hanafites -- Turkey -- History; Turkey -- History -- Ottoman Empire, 1288-1918.